Research on the influence of the visual perception characteristics of fitness trail landscape space based on psychological perception: a case study of Hunnan District, Shenyang, China - Zhu, Wenli; Chen, Zikun; Wang, Xiaojun; Hu, Feng (Frontiers in Psychology, 2025)
Based on the multidisciplinary method of collaborative psychology, sociology and environmental design research, this study conducts a quantitative study on the relationship between the visual perception of fitness trail landscape space and the psychological perceptions of fitness activities, providing data-driven references for the design of fitness trials. First, self-image acquisition is used to form a fitness trail landscape space image material library including 646 pictures. Second, we identify the user preferences for the composition of the main landscape elements of fitness trails, with subsequent research focusing on the top two preference combinations, namely, “plant–plant” and “plant–water.” Third, on the basis of the results of the semistructured interviews, a word frequency analysis is conducted, and the visual perception feature index framework of the fitness trail landscape space containing 12 indicators is constructed in combination with the relevant literature. An image semantic segmentation process, along with manual auditing, is applied to the self-collected images, resulting in a dataset of visual perception characteristic indicators. Furthermore, based on the KANO model, a psychological perception evaluation framework is constructed, and psychological perception evaluation datasets are obtained by using the semantic differential (SD) method. Finally, correlation analysis, multiple regression, and curve fitting are applied to the two datasets and the relevant threshold ranges are obtained. The results show that within the “plant–plant” combination, the optimal threshold for the degree of enclosure is 66–81%, the optimal threshold for the green view rate is 62–78%, the optimal threshold for the degree of openness of the sky is 2.2–3.2%, and the optimal threshold for the building façade area ratio is 0–10%. For the “plant–water” combination, the optimal threshold for the green view rate is 58–68%, the optimal threshold for the openness of the sky is 4.1–6.0%, the optimal threshold for the water area ratio is 0.75–1.75%, and the optimal threshold for the road area ratio is 33–43%.